Strengthening the Three Lines of Defence in Terms of More Efficient Operational Risk Management in Central Banks - Radoica Luburić (Journal of Central Banking Theory and Practice, 2017)
This paper is the result of the author's many years of multidisciplinary research in the areas of quality management and operational risk management. The main focus of the research is aimed at strengthening the model of the "three lines of defence" in terms of more efficient management of operational risks - those that arise as a result of inadequate and unsuccessful processes and systems, human factors, as well as those that can appear as a result of external events. The strengthening of the three lines of defence model is brought about through the synergy of quality management principles, the principles of risk management, and the total quality management approach. In essence, the term strengthening may be interpreted as a process of continual improvement. Business operations based on the principles of quality management and risk management allow central banks to be able to continuously improve their overall business performance. The principles of quality management contain properly aligned and matched best solutions from current management theory and practice. Designed to work together - and this essentially means in a consistent, synchronized and synergistic manner, the principles are translated into a series of requirements and guidelines of international standards suitable for implementation. Through their synergy, the principles of quality management and risk management, as well as approaches to total quality management form a clear, applicable and sustainable paradigm of successful management of central banks. Incorporation of the principles of quality management in central bank systems and processes would significantly strengthen the three lines of defence, in terms of efficient operational risk management, which this paper aims to show in a clear and comprehensive manner. Although any central bank is a specific institution, all the principles of quality management and risk management can be applied to its operations. In addition to the numerous and highly significant benefits and synergistic effects that the application of quality management and risk management principles bring to central banks, what should also be highlighted is their impact on a new way of thinking regarding successful central bank governance, which generates a new attitude towards its responsibilities, objectives, employees, and the environment. A new way of thinking produces new behaviours and an improved business culture and can ensure the sustainable success of central banks and other financial system entities. Bearing in mind that the process of risk management is an integral part of the working of central banks, the most effective results are achieved when the "process owner" is also the "risk owner". This paper shows that the integration of these two roles contributes to the full effectiveness and efficiency of the processes and risks management. It is clearly demonstrated that this unity of the roles, along with a quality culture, a risk culture, and risk-based thinking is embedded in all management processes - from defining policies, objectives, and plans, all the way to their operational implementation and that this ensures the fulfilment of requirements, needs, and expectations of customers and other relevant stakeholders. In all of this, the management of any central bank plays the most important role, not only because of the importance and complexity of the issues in question, but also because of their full responsibility to manage risks in a proper, effective, conscientious and dedicated manner, as that is the key precondition for achieving sustainable success.
Keywords: E58; G31; 330; strengthening the three lines of defence; operational risk management; strengthening the first line of defence; strengthening the second line of defence; strengthening the third line of defence; harmonisation and coordination of the strengthened three lines of defence model; central banks.